2019
DOI: 10.3400/avd.cr.19-00047
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Abdominal Aortic Aneurysm with a Duplicated Inferior Vena Cava

Abstract: We report a very rare case of a ruptured abdominal aortic aneurysm (AAA) with an anomaly of the inferior vena cava (IVC). The AAA was covered with a large hematoma and an expanded vein was on its left side. It was not until we could not locate the IVC on the right side of AAA that we recognized the anomaly during the operation. Although we reviewed the findings on enhanced computed tomography, we were confused whether the case was a duplicated or left-sided IVC. Subsequently, a bifurcated vascular prosthesis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…If unidentified, risks may be heightened. 2,3 As an example, one case report showed that a misdiagnosis of the left IVC as the left renal vein and subsequent inadvertent ligation of the left IVC led to deep vein thrombosis in the iliac and deep leg veins. 4 Preoperative identification is especially important for renal surgery, done by laparoscopic approaches, where a limited field of view can pose challenges for the identification of vascular anomalies.…”
Section: Cuaj -Images In Urologymentioning
confidence: 99%
“…If unidentified, risks may be heightened. 2,3 As an example, one case report showed that a misdiagnosis of the left IVC as the left renal vein and subsequent inadvertent ligation of the left IVC led to deep vein thrombosis in the iliac and deep leg veins. 4 Preoperative identification is especially important for renal surgery, done by laparoscopic approaches, where a limited field of view can pose challenges for the identification of vascular anomalies.…”
Section: Cuaj -Images In Urologymentioning
confidence: 99%